PPAR-γ Agonists and Their Role in Primary Cicatricial Alopecia - Sarawin Harnchoowong; Poonkiat Suchonwanit (PPAR Research)
Peroxisome proliferator-activated receptor γ (PPAR-γ) is a ligand-activated nuclear receptor that regulates the transcription of various genes. PPAR-γ plays roles in lipid homeostasis, sebocyte maturation, and peroxisome biogenesis and has shown anti-inflammatory effects. PPAR-γ is highly expressed in human sebaceous glands. Disruption of PPAR-γ is believed to be one of the mechanisms of primary cicatricial alopecia (PCA) pathogenesis, causing pilosebaceous dysfunction leading to follicular inflammation. In this review article, we discuss the pathogenesis of PCA with a focus on PPAR-γ involvement in pathogenesis of lichen planopilaris (LPP), the most common lymphocytic form of PCA. We also discuss clinical trials utilizing PPAR-agonists in PCA treatment.